Antibiotic Self-Medication Behavior at Waras Lestari Pharmacy - Wibowo, Kevin Rachmalia; Peristiowati, Yuly; Agustin Widyowari (Innovative Approaches in Health Science Journal, 2025)
Background: The use of antibiotics without a doctor's prescription is a widespread phenomenon in communities around the world, including in Indonesia. According to data from Waras Lestari Pharmacy, 253 patients self-medicated with antibiotics. Preliminary interviews revealed that people tend to self-medicate based on previous experiences and recommendations from friends or family. Healthcare workers, particularly pharmacists, have a critical role to take firm action against selling antibiotics without a prescription and to provide appropriate treatment advice to address patient complaints. This prompted researchers to conduct a study on antibiotic self-medicating behavior at Waras Lestari Pharmacy in Kediri City. Methods: The approach used in this research uses a qualitative approach. The informants in this study were patients who purchased antibiotics without a prescription at Waras Lestari Pharmacy in Kediri City. The sampling technique used was purposive sampling. Data collection from informants by means of interviews. Results: In this study, all informants self-medicated with antibiotics without a doctor's prescription at the Waras Lestari Pharmacy in Kediri City. Predisposing factors, such as perceptions and beliefs, significantly influenced self-medicating. Enabling factors, such as the availability of readily accessible antibiotics in pharmacies without strict supervision, were the main factors driving self-medicating behavior. Reinforcing factors: Previous personal experience was the dominant reinforcing factor. Informants tended to purchase the same antibiotics that doctors had prescribed for similar complaints in the past, confident in their effectiveness. Conclusion: Overall, antibiotic self-medication behavior at Waras Lestari Pharmacy in Kediri City remained high, with various predisposing, enabling, and reinforcing factors contributing. This study also found gaps in the oversight of antibiotic self-medication practices, both in terms of regulation and education, which is an important finding for improving the pharmaceutical care system in the community.